Analisis Keamanan Jaringan Menggunakan Metode Security Policy Development Life Cycle (SPDLC) - Yunanri W; Yuliadi Yuliadi; Shinta Esabella; Yasinta Bella Fitriana (STMIK Budi Darma, 2023)
Security is a system for carrying out prevention on a network that can be done using various methods, such as firewalls, port scanning, and DDoS. A firewall is a security system that can open or close certain port access through the firewall on the router according to the role that is built. One of the network security methods applied to Mikrotik Router OS is Port Knocking, which opens or closes certain port access through the firewall on the router according to the role that is built. However, a common problem that is often experienced in the provision of internet services such as the security network of the Tapangpass Cafe network is the problem of access rights. Several problems are encountered such as the need for internet in network security, so there is concern about hacking on the proxy network, therefore researchers will conduct an analysis on network security at Tangpass Cafe. Using the Security policy development life cycle method, then the results of this analysis researchers apply firewall network security from port scanning and denial of service attacks. The test results on the Tapangpass Café Mikrotik network are vulnerable to attack gaps, so security is needed on the firewall rules, Secure Routerboard RB941-2nD Settings, Periodic testing on the network used, and Upgrade the Operating System on Mikrotik